DAKWAH PADA MASA NABI MUHAMMAD SAW. (STUDI NASKAH DAKWAH NABI MUHAMMAD PADA PERIODE MADINAH) - Sitti Nasriah (Jurnal Dakwah Tabligh, 2016)
On the stage of history, propagation of the Prophet is divided into two periodisations namely the period of Mecca and Medina. Both of these periods have their own character and strategy, this can be seen from the extent to which the results achieved by the Prophet in the period of Mecca and Medina. Historians give categorization that Prophet's propagation in Mecca is characterized by aqidah planting mission to the ummah, while in Madinah it is more inclined towards social and legal development. In Medina, the Prophet Muhammad. Continue broadcasting Islam to the inhabitants of the unbelieving Madinah. He invited the Jews and Christians to believe in him. Some of them were converts to Islam, but most of them held their religion firmly.